Analisis Dampak Upah dalam Meningkatkan Kesejahteraan Buruh Tani Menurut Perspektif Ekonomi Islam : Studi Kasus: Di Jorong Kartini, Kecematan Gunung Tuleh, Kabupaten Pasaman Barat (Jurnal Ekonomi Bisnis dan Akuntansi, 2025)
This research aims to find out the factors that cause people in Jorong Kartini to work more as agricultural laborers and what impact wages have on improving the welfare of agricultural laborers in Jorong Kartini. The type of research that the author uses is field research and uses qualitative research methods. Data collection techniques used were interviews, observation and documentation. The data analysis technique used is descriptive qualitative. The stages carried out are Data Reduction, Data Presentation, and Drawing Conclusions. From the results of research conducted in the field, it can be concluded that the wages earned by agricultural workers have not had an impact on welfare, where the wages they receive only fulfill basic needs, such as food, drink and clothing. Meanwhile, many people in Jorong Kartini work as agricultural laborers, factors such as very high economic needs, low income so that it is not enough to meet their needs, consumption and family expenses are always increasing, housing conditions, education, where those who work as agricultural laborers do not need a high level of education. such as only elementary, middle and high school graduates, personal desires and the absence of the government's role for people who do not have permanent jobs.